Dampak Gibah Terhadap Kesehatan Mental Pada Mahasiswa Fakultas Ushuluddin dan Pemikiran Islam UIN Raden Fatah Palembang - Vina Selvia Meisopa; Apriyanti; Yulian Rama Pri Handiki (CV. ITTC INDONESIA, 2024)
Humans are social creatures who need each other and live in groups. As social creatures, of course, humans cannot be separated from the relationship of interaction and communication in everyday life using the tongue. The tongue is one of the limbs given by Allah Swt so that humans can express what is in their hearts. However, not everything that is contained in the heart is good to be expressed through the tongue, because Allah Swt commands humans to keep the tongue. However, people today often follow their lusts and cannot protect their tongues, which leads to gibah. The purpose of this research is to find out the factors and influences that become the background of the occurrence of gibah among students of the Faculty of Ushuluddin and Islamic Thought. This research method uses Qualitative Research, which is a type of field research. This research is based on field data related to the research topic. The qualitative approach is expected to produce an in-depth description of the speech, writing, or observable behavior of an individual or group. Data collection techniques through interviews and observations. Data analysis used includes data reduction, data display and conclusion drawing / verification. The results showed that gibah affects the mental health of students of the Faculty of Ushuluddin and Islamic Thought in several ways, namely: Increased stress and anxiety, reduced quality of social relationships, lower self-confidence, negative thought patterns, impaired focus and productivity, and guilt.